Verbal cues to deceit when lying through omitting information - Leal, Sharon (Legal and criminological psychology, 2020)
BACKGROUND-Lying through omitting information has been neglected in verbal lie detection research. The task is challenging: Can we decipher from the truthful information a lie teller provides that s/he is hiding something? We expected this to be the case because of lie tellers’ inclination to keep their stories simple. We predicted lie tellers to provide fewer details and fewer complications than truth tellers, the latter particularly after exposure to a Model Statement.METHOD-A total of 44 truth tellers and 41 lie tellers were interviewed about a conversation (debriefing interview) they had taken part in earlier. Lie tellers were asked not to discuss one aspect of that debriefing interview.RESULTS-Results showed that truth tellers reported more complications than lie tellers after exposure to a Model Statement.CONCLUSION-Ideas about future research in lying through omissions are discussed.